PENGARUH PELATIHAN "THE SECRET MEANING OF BROKER" TERHADAP KETERIKATAN KERJA PADA BROKER SAHAM - Karlina, Yovita; Probowati, Yusti (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
The purpose of this research is to know about correlation of work meaning as a calling and workengagement in Broker work life. How âthe secret meaning of brokerâ training can improve thelevel of work engagement. This research discuss about Job Resources and PersonalResources as a factor to predict high or low level of work engagement. The method of thisresearch is single case experimental pretest-posttest only. Participant (N=15) is the populationof PT.X Securities. The method of data collection using questionnaire, observation andinterview. The result of this research âthe secret meaning of brokerâ training as a personalresources and job resources as a environmental, supervisory, organization system, socialsupport togetherness increased work engagement.